Guiding Principles in The Study of Neighborhoods as a Basis for the city Formation and Its Development "Homs city as a case of study": المبادئ التوجيهية في دراسة المجاورات السكنية كأساس لتشكيل المدينة وتطوّرها "مدينة حمص كحالة دراسية" - Rolana Jamil Rabih, Razan Jihad Mtanus (Journal of engineering sciences and information technology, 2021)
The city has grown and developed with time over several eras, and at each stage different concepts were defined in city planning, such as the residential neighborhood theory that Berry identified and considered it as the smallest planning unit that contributes to the formation of the city. The concepts of residential neighborhood have developed by a number of planners and have social, economic and urban dimensions. It is essential that it cannot be ignored when developing any plan for neighborhoods or cities, but these dimensions have differed between countries and planners, and it was necessary to set some guidelines in their planning as a primary goal to show their role in the formation of cities as the smallest component in the city formation in order to avoid the many problems In the processes of urban, population and economic development in general.From this logic, the research dealt with a theoretical and analytical study of the theoretical concepts of residential neighborhoods for some planners and identifying the elements of residential neighborhoods and their basic components in order to reach an analytical approach to assess residential neighborhoods and determine the guidelines for their study. Then, some international, Arab and local experiences were studied according to those principles in order to draw some important results, and project them to the city of Homs to demonstrate the importance and role of residential neighborhoods as a basis for the formation and development of residential neighborhoods and cities.The guidelines necessary to be available in the study of residential neighborhoods were deduced, and by conducting a comparative approach between the research experiences,  it was noted that the environmental and regional dimension was provided in most by 100%, as well as the availability of the appropriate radius by 90%, except that there are bicycles and pedestrians paths and the movement of people with special needs was 10% which needs to be developed and improved.The research recommends adoption the concluded guidelines because they include all urban and planning aspects and meet the resident social and economic needs and thus contribute to the city formation (urban, economic and social). The research also recommends following a basic idea in the study of the neighborhood so that it achieves the possibility of dividing it into residential groups that contain service centers according to radii suitable for the movement of the population on foot (between 400- 500 m) with securing an area for regional or city services, and attention to sustainability and the provision of the green element. And work to limit the movement of pedestrians according to special paths, taking into account the movement of people with special needs, and securing the necessary site coordination elements.